9-Phenyl-9-phosphafluorene oxide based organic ligands synthesized via successive SNAr reactions and their symmetric phosphorescent Ir(III) complexes for highly efficient solution-processed OLEDs. (January 2023) - Deng, Xuming; Liu, Siqi; Sun, Yuling; Zhong, Daokun; Jia, Dongming; Yang, Xiaolong; Su, Bochao; Sun, Yuanhui; Zhou, Guijiang; Jiao, Bo; Wu, Zhaoxin
Abstract: Three organic ligands with 9-phenyl-9-phosphafluorene oxide (PhFlPO) group have been synthesized via successive nucleophilic aromatic substitution (SN Ar) reactions between dibenzothiophene dioxides and PhPH2 -KOH under mild reaction conditions at room temperature. In this way, the novel PhFlPO-type organic ligands can be easily obtained without either highly sensitive Grignard or organolithium reagents of noble metal catalysts. Using these PhFlPO-type organic ligands, cyclometalated Ir(III) phosphorescent complexes with PhFlPO groups have been developed through well-accepted two-step strategy. To the best of our knowledge, these complexes represent the unprecedented examples of symmetric cyclometalated Ir(III) phosphorescent complexes bearing PhFlPO group. It has been found that electron-density on the coordinated carbon atom in the PhFlPO unit can exert a significant influence on the metal-to-ligand charge transfer transition (MLCT) processes and phosphorescent emission behavior of these cyclometalated Ir(III) phosphorescent complexes. In addition, the electroluminescent potential of these new cyclometalated Ir(III) phosphorescent complexes with PhFlPO groups has been characterized in solution-processed organic light-emitting diodes (OLEDs). They can show very impressively high external quantum efficiency (ηext ), current efficiency (ηL ) and power efficiency (ηP ) of 20.0%, 71.7 cd A −1 and 56.1 lm W −1, respectively. These encouraging research results can furnish critical information for developing new PhFlPO-based Ir(III) phosphorescent emitters. Graphical abstract: Phosphorescent Ir(III) complexes with 9-Phenyl-9-phosphafluorene oxide organic ligands for highly efficient solution-processed OLEDs. Image 1 Highlights: Synthesis of ligands with 9-phenyl-9-phosphafluorene oxide group by successive nucleophilic aromatic substitution reactions. Organic ligands with pyridyl group substituted on different position on the 9-phenyl-9-phosphafluorene oxide unit. Symmetric Ir(III) phosphorescent complexes with 9-phenyl-9-phosphafluorene oxide group showing high EL efficiencies.